Simple Resistance Exercise helps Patients with Non-alcoholic Fatty Liver Disease - Takahashi, A.; Abe, K.; Usami, K.; Imaizumi, H.; Hayashi, M.; Okai, K.; Kanno, Y.; Tanji, N.; Watanabe, H.; Ohira, H. (International Journal of Sports Medicine, 2015)
To date, only limited evidence has supported the notion that resistance exercise positively impacts non-alcoholic fatty liver disease. We evaluated the effects of resistance exercise on the metabolic parameters of non-alcoholic fatty liver disease (NAFLD) in 53 patients who were assigned to either a group that performed push-ups and squats 3 times weekly for 12 weeks (exercise group; n=31) or a group that did not (control; n=22). Patients in the control group proceeded with regular physical activities under a restricted diet throughout the study. The effects of the exercise were compared between the 2 groups after 12 weeks. Fat-free mass and muscle mass significantly increased, whereas hepatic steatosis grade, mean insulin and ferritin levels, and the homeostasis model assessment-estimated insulin resistance index were significantly decreased in the exercise group. Compliance with the resistance exercise program did not significantly correlate with patient background characteristics such as age, sex, BMI and metabolic complications. These findings show that resistance exercise comprising squats and push-ups helps to improve the characteristics of metabolic syndrome in patients with non-alcoholic fatty liver disease.
Keywords: push-ups; squats; NAFLD